Challenges in lipid production from lignocellulosic biomass using Rhodosporidium sp.; A look at the role of lignocellulosic inhibitors. (13th December 2018) - Osorio‐González, Carlos S.; Hegde, Krishnamoorthy; Brar, Satinder K; Kermanshahipour, Azadeh; Avalos‐Ramírez, Antonio
Abstract: The use of lignocellulosic biomass biofuels is an attractive alternative because they do not put food safety at risk, they are a renewable source, and their use is limited. The use of microorganisms has now become more widespread to take advantage of the carbohydrates present in this raw material (cellulose and hemicellulose) and the products of its hydrolysis (glucose, xylose, arabinose, galactose, and mannose). The fatty acids obtained from oleaginous microorganisms are potential sources for the production of drop‐in biofuels. Rhodosporidium sp. is an oleaginous yeast that accumulates up to 70% of its biomass in the form of lipids and is highly adaptable to different types of substrates. This review discusses the different factors and challenges (genetic modification of strains, pretreatments, and inhibitor effects) in obtaining lipid from lignocellulosic biomass using Rhodosporidium sp. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd